Nutritional Therapy in Adult Hirschsprung Disease Post-Total Colectomy and Ileostomy with Severe Protein-Energy Malnutrition: A Case Report - Faradilah, Andi; Christine Rogahang; Nurbaya Syam; Agussalim Bukhari (Alami Journal (Alauddin Islamic Medical) Journal, 2025)
Adult Hirschsprung disease, also known as congenital aganglionic megacolon, is a rare congenital disorder characterized by the absence of ganglion cells in the distal segment of the large intestine, diagnosed in adulthood. Impaired nutrient absorption due to the dysfunctional intestinal segment can lead to malabsorption and malnutrition. A 23-year-old female presented with severe protein-energy malnutrition after total colectomy surgery for suspected adult Hirschsprung disease. She had a history of chronic constipation from childhood, abdominal pain, and abdominal distension. She was referred to a clinical nutritionist 2 days post-surgery. The nutrition therapy started with oral and parenteral nutrition, gradually increasing macronutrient requirements based on clinical condition and gastrointestinal tolerance.  On the 12th day post-total colectomy surgery, she developed complications of obstructive ileus, requiring ileostomy. Laboratory tests showed signs of inflammation. Nutritional support for adult Hirschsprung disease focuses on meeting energy requirements, enhancing nutrient absorption after abdominal surgery, and minimizing post-operative inflammation.